Spider Fauna of Navdanya Biodiversity Farm, Uttarakhand, India - Anil Kumar, Pooja A.; Quasin, Shazia; Sree Lekshmi; Uniyal, Virendra Prasad (Indian Forester, 2019)
Spiders are abundant in most terrestrial ecosystems forming one of the dominant macro-invertebrate predator groups. They are sensitive to a wide range of environmental factors including topography, season and other microhabitat factors. Considering their role in the ecosystem, in the present study, we attempted to investigate the diversity and composition of the spiders in Navdanya Biodiversity Farm, Uttarakhand, India. The habitat types that were selected for sampling are mango farm, herbal garden and other crop fields such as brinjal, tomato etc. Sampling was carried out in the month of June 2016. Spider specimens were collected randomly by using five semi quantitative techniques viz., ground hand collection, aerial hand collection, sweep netting, litter sampling and beating method. A total of 112 spider specimens representing 52 species coming under 33 genera belonging to 14 families were collected from Navdanya farm. Salticidae was the dominant family. High generic diversity was found in Salticidae reporting 9 genera. Oxyopes species were active in controlling insects that could be potential pests. A total of 7 feeding guilds were identified by the analysis of feeding behaviour of collected spiders. This study is also the first documentation of the spider fauna in Navdanya Biodiversity Farm, Uttarakhand, India.